Using proton radiation from the moon to search for diurnal variation of regolith hydrogenation. (1st November 2018) - Schwadron, N.A.; Wilson, J.K.; Jordan, A.P.; Looper, M.D.; Zeitlin, C.; Townsend, L.W.; Spence, H.E.; Legere, J.; Bloser, P.; Farrell, W.M.; Hurley, D.; Petro, N.; et al.
Abstract: With the help of a new observing technique, we have detected diurnal variations in both lunar albedo protons and incident galactic cosmic rays (GCRs) at the Moon. Using the Cosmic Ray Telescope for the Effects of Radiation (CRaTER) instrument on the Lunar Reconnaissance Orbiter (LRO), we have combined specific, targeted observations of the lunar horizon with our nominal nadir-viewing data to find a tentative enhancement in the yield of lunar albedo protons at the local sunrise terminator of the Moon relative to the local sunset terminator. A diurnal variation in hydrogenation in the top few cm of regolith is one possible interpretation of this result. We have also measured an unanticipated AM/PM difference in the arriving GCRs at the Moon which can be explained by a known streaming anisotropy. The relatively small data set used here (compared to previous mapping studies of CRaTER data) and heretofore untried horizon observations required us to develop improved data analysis techniques, which we will use in the future to revisit previous data sets and to analyze planned new horizon observations of lunar albedo protons. Highlights: Improved observing technique for analyzing albedo protons. Tentative detection of diurnal variations in lunar albedo protons. Detection of diurnal variations in incident galactic cosmic rays.